Get the answers you need at Westonci.ca, where our expert community is always ready to help with accurate information. Get quick and reliable solutions to your questions from a community of experienced professionals on our platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
Answer:
X = 0
Y = -2
Step-by-step explanation:
3x = 4y + 8
x = (4y + 8)/3
18 [(4y + 8)/3] - 5y = 10
6(4y + 8) - 5y = 10
24y + 48 - 5y = 10
19y = -38
y = -2 (Plug y into either one of the original formulas.)
18x - 5(-2) = 10
18x + 10 = 10
18x = 0
x = 0 (Check your work to make sure you have correct answers.)
3(0) - 4(-2) = 8
0 + 8 = 8
8 = 8 ;)
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.